2021
DOI: 10.1038/s41598-021-01624-5
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible N-acetyl-nanoconstruct alleviates lipopolysaccharide-induced acute lung injury in vivo

Abstract: Oxidative stress plays important roles in inflammatory responses during acute lung injury (ALI). Recently, nanoconstruct (Nano)-based drug-delivery systems have shown promise in many models of inflammation. In this study, we evaluated the anti-inflammatory effects of N-acetylcysteine (NAC) loaded in a biocompatible Nano using a rat model of ALI. We synthesized a Nano with a good NAC-releasing capacity using porous silica Nano, which was used to produce Nano/NAC complexes. For in vivo experiments, Sprague–Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Meanwhile, collagen causes contraction problems during gelation, especially at the interface between collagen and MSN-containing PBS, where diffusion of MSNs starts. To minimize contraction-related problems at the gel–liquid interface and detachment of collagen from the surface, PDA was coated inside the center channel, , which mitigated notable detachment or inhomogeneity of collagen. Nevertheless, because of the contraction of collagen during the gelation process while maintaining wetting of PDMS microposts, the geometry of the gel–liquid interface inevitably deviated from the straight line, and the utilization of interface images for analysis might cause inadequacy because of incorrect fluorescence information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, collagen causes contraction problems during gelation, especially at the interface between collagen and MSN-containing PBS, where diffusion of MSNs starts. To minimize contraction-related problems at the gel–liquid interface and detachment of collagen from the surface, PDA was coated inside the center channel, , which mitigated notable detachment or inhomogeneity of collagen. Nevertheless, because of the contraction of collagen during the gelation process while maintaining wetting of PDMS microposts, the geometry of the gel–liquid interface inevitably deviated from the straight line, and the utilization of interface images for analysis might cause inadequacy because of incorrect fluorescence information.…”
Section: Resultsmentioning
confidence: 99%
“…MSNs were prepared according to a previously reported sol–gel method with modification. , CTAB with TMOS or TEOS was used as a control for pH conditions for an appropriate catalytic reaction. For 10 nm particles, CTAB (83.8 mg) and TMOS (0.096 mL) were reacted in an ammonium hydroxide/ethanol solution at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A study on a mechanically ventilated rat with lipopolysaccharide-induced ALI reported that a high dose of NAC reduced oxidative damage and inflammatory cell in the histology of the lungs [14]. Other studies also reported that NAC treatment protected against lipopolysaccharide-induced ALI [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing NF-κB activity and associated proinflammatory cytokines, these particles also increased antiinflammatory cytokine interleukin-10 (IL-10) (Vuong et al, 2017). Other anti-inflammatory and antioxidant polymers that have demonstrated protection from LPS include N-acetylcysteine gels (Kim et al, 2021), graphene oxide-polypropylene nanoparticles (Fonticoli et al, 2023), and polyphenol gels (Luque et al, 2023), the latter two of which also have antibacterial benefits. In a cecalpuncture and ligation sepsis mouse model, dendrimers scavenged pro-inflammatory cytokines, resulting in a significantly improved survival rate of 100% (Shi et al, 2020).…”
Section: Synthetic Biomaterials For Inflammationmentioning
confidence: 99%